The use of bone-turnover markers in asia-pacific populations - Vasikaran, Samuel; Thambiah, Subashini C.; Tan, Rui Zhen; Loh, Tze Ping (Korean Society for Laboratory Medicine, 2023)
Bone-turnover marker (BTM) measurements in the blood or urine reflect the bone-remodeling rate and may be useful for studying and clinically managing metabolic bone diseases. Substantial evidence supporting the diagnostic use of BTMs has accumulated in recent years, together with the publication of several guidelines. Most clinical trials and observational and reference-interval studies have been performed in the Northern Hemisphere and have mainly involved Caucasian populations. This review focuses on the available data for populations from the Asia-Pacific region and offers guidance for using BTMs as diagnostic biomarkers in these populations. The procollagen I N-terminal propeptide and β-isomerized C-terminal telopeptide of type-I collagen (measured in plasma) are reference BTMs used for investigating osteoporosis in clinical settings. Premenopausal reference intervals (established for use with Asia-Pacific populations) and reference change values and treatment targets (used to monitor osteoporosis treatment) help guide the management of osteoporosis. Measuring BTMs that are not affected by renal failure, such as the bone-specific isoenzyme alkaline phosphatase and tartrate-resistant acid phosphatase 5b, may be advantageous for patients with advanced chronic kidney disease. Further studies of the use of BTMs in individuals with metabolic bone disease, coupled with the harmonization of commercial assays to provide equivalent results, will further enhance their clinical applications.